Integrating scientific and local knowledge to address conservation conflicts: Towards a practical framework based on lessons learned from a Scottish case study. Issue 107 (May 2020) - Ainsworth, Gillian Barbara; Redpath, Stephen Mark; Wilson, Mark; Wernham, Chris; Young, Juliette Claire
Highlights: In conservation conflict situations, values and practices are central to the dispute. Single participatory, knowledge-based approaches help but cannot transform conflicts. Our approach merges five complimentary theoretical approaches for mapping conflict. We advise how to address known challenges for achieving knowledge integration goals. Our practical framework and novel considerations can inform processes such as IPBES. Abstract: Integrating local knowledge with scientific knowledge can offer significant benefits to improving environmental decision-making. However, this is especially challenging in environmental conflict situations where advice is lacking, and no single approach can foster conflict transformation. To understand stakeholder knowledge and its integration in a conflict transformation process in Scotland, we brought together diverse stakeholder organisations and encouraged power sharing in the project's management. Our mixed-methods approach was based on theories of community science, knowledge co-production, knowledge integration and implementation and conflict transformation. We gathered stakeholder perceptions to see where local and scientific knowledge converged and diverged. Stakeholders holding opposing views mutually prioritised knowledge gaps and identified future collaborative actions. Building upon lessons learned, we present a practical framework and associated considerations to realise knowledge integration goals in conservation conflict situations. This framework is widely applicable, especially in situations where disputes over the evidence-base prevent positive outcomes for people and nature.